San Jose State Normal School Pennant 1902-03 (March 1902) - San Jose State Normal School:::Creator::::::::::::; Little, Elsie:::Contributor:::::::::::: (Students of the State Normal School at San Jose)
Volume 5, number 7. The Normal Pennant was a student magazine published and edited by students with assistance from the English Department and occasionally a panel of outside judges. It consisted of students' poems, short stories, essays, plays, parody and news along with advertisements by local businesses and services.